Abelard's love [Abaelards Liebe] - Rinser, Luise 1911-2002; Snook, Jean M. 1952- (Lincoln University of Nebraska Press, 1998)
The doomed romance of Abelard, a 12th century French teacher of philosophy and his pupil, Heloise, which led to his castration and her confinement in a convent. The relationship is recounted in the form of letters, written to Heloise by their son, Astrolabe.
Keywords: Abelard, Peter -- 1079-1142 -- Fiction; Hâeloèise -- approximately 1095-1163 or 1164 -- Fiction